Pengaruh Daya Tarik Wisata, Keselamatan, dan Sarana Wisata terhadap Kepuasan Serta Dampaknya Terhadap Loyalitas Wisatawan: Studi Community Based Tourism di Gunung Api Purba Nglanggeran - Hary Hermawan (Media Wisata, 2017)
Loyalty has become a serious concern for the managers of tourist villages because the loyalty of tourists is a guarantee of tourism business be sustainable. The purpose of this study is to examine how the loyalty of tourists can be created by the factors of the tourist attraction, safety, and amenities, with loyalty as an intervening, on the model of Community-Based Tourism development in Gunung Api Purba Nglanggeran Tourism Village. The analytical method used is path analysis with Partial Least Square (PLS). The results showed that tourist attraction is a dominant factor that gives a positive influence on the loyalty of tourists through intervention variable satisfaction. Other factors studied, namely safety and tourist facilities are not proven to affect the loyalty of tourists. This research recommends that loyalty of tourists can be achieved through efforts to improve the quality of tourist attraction